THE EFFECT OF TEACHING STYLE AND MOTIVATION ON FOOTBALL DRIBBLING LEARNING OUTCOMES OF STUDENTS OF SMA 2 TAKENGON - Sahabul Adri AR; Didi Yudha Pranata; Nugraha Pratama; Helminsyah Helminsyah; Sugiharto Sugiharto (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2026)
This study aims to determine: 1) the difference in the influence between the Teaching Style of Practice, the Inclusion teaching style on the learning outcomes of soccer dribbling , 2) the difference in the influence between high and low levels of motivation on the learning outcomes of soccer dribbling, 3) there is an interaction between teaching style and motivation on the learning outcomes of soccer dribbling. This study uses an experimental method with a 2 x 2 factorial design. The research population of students amounted to 175 people and the sample used in this study amounted to 44 people with a purposive sampling technique, consisting of 22 students with high motivation and 22 students with low motivation. The results of the study showed that the results of the pre-test dribbling in soccer games using the Teaching Style of Practice from 22 students who were sampled in this study showed that the results of the pre-test dribbling in soccer games averaged 62.70. The results of the post-test dribbling in soccer games averaged 85.23, resulting in an increase in value of 22.53. Meanwhile, the results of dribbling learning in soccer games using an inclusive teaching style from 22 students sampled in this study showed that the average dribbling pre-test result in soccer games was 62.72. The average dribbling post-test result in soccer games was 82.98, resulting in an increase in value of 20.25.